Double‐Gate MoS2 Field‐Effect Transistors with Full‐Range Tunable Threshold Voltage for Multifunctional Logic Circuits. Issue 27 (31st May 2021) - Yi, Jiali; Sun, Xingxia; Zhu, Chenguang; Li, Shengman; Liu, Yong; Zhu, Xiaoli; You, Wenxia; Liang, Delang; Shuai, Qin; Wu, Yanqing; Li, Dong; Pan, Anlian
Abstract: Multifunctional reconfigurable devices, with higher information capacity, smaller size, and more functions, are urgently needed and draw most attention in frontiers in information technology. 2D semiconductors, ascribing to ultrathin body and easy electrostatic control, show great potential in developing reconfigurable functional units. This work proposes a novel double‐gate field‐effect transistor architecture with equal top and bottom gate (TG and BG) and realizes flexible optimization of the subthreshold swing (SS) and threshold voltage ( V TH ). While the TG and BG are used simultaneously, as a single gate to drive the transistor, ultralow average SS value of 65.5 mV dec −1 can be obtained in a large current range over 10 4, enabling the application in high gain inverter. While one gate is used to initialize the channel doping, full logic swing inverter circuit with high noise margin (over 90%) is demonstrated. Such device prototype is further extended for designing reconfigurable logic applications and can be dynamically switched and well maintained between binary and ternary logics. This study provides important concept and device prototype for future multifunctional logic applications. Abstract : A double‐gate MoS2 field‐effect transistor is designed for potential applications in multifunctional reconfigurable logic circuits. Featuring the feasible tuning of threshold voltage and optimizing of subthreshold swing of the transistors, the system can both function well as full logic swing binary logic with high noise margin and be dynamically reconfigured between binary and ternary logic.